Rekonseptualisasi Alokasi Lahan Pertanian dalam Undang-Undang Cipta Kerja Berdasarkan Perspektif Islam - Risman Ramadwika; Ujang Maman; Achmad Tjahja Nugraha; Iwan Aminudin (Paspalum: Jurnal Ilmiah Pertanian, 2023)
The Job Creation Law is aimed at improving the business climate in order to facilitate investment. However, a number of laws that have been revised by the Job Creation Law have caused a flurry of rejection because they are seen as efforts to liberalize land. This is also a threat to the management of agricultural land in Indonesia because agricultural land is the main determinant of production activities for farmers. Meanwhile, Islam has a fair management concept of agricultural land. The purpose of this study is to explain the concept of agricultural land allocation according to the Job Creation Law based on an Islamic perspective. In addition, this study also aims to explain alternative solutions for allocating agricultural land in Indonesia that are inclusive even though it uses an Islamic perspective. oriented towards the interests of corporations and investors. The concept of agricultural land allocation policies based on an Islamic perspective is based on theological values to ensure that Islamic political economy goals can be achieved by prioritizing the poor. There are two concepts of agricultural land allocation in Indonesia based on an Islamic perspective that can be recommended, namely: (1) the concept of utilization of state land; and (2) the concept of agricultural land waqf.